2007
DOI: 10.5897/ajb2007.000-2428
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, biochemical and molecular characterization of 2-chlorophenol-degrading Bacillus isolates

Abstract: Pure cultures of 2-chlorophenol degrading bacteria were isolated from a natural enrichment that may be adapted to chlorophenols in the industrial zone at Umm-Saied city (Qatar). The bacteria were identified by 16S rDNA analysis, using PCR with universal primers. Comparative analysis of the 16S rDNA sequence (~ 550 bp) in the GenBank database revealed that these bacteria are related to the genus Bacillus. Molecular heterogeneity among 2-chlorophenol-degrading bacteria was investigated using REP-PCR chromosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The presence of a clear area surrounding the colony is a signi cant indication of biosurfactant production. Bacteria with positive hemolysis were selected for supplementary tests [13].…”
Section: Hemolytic Activitymentioning
confidence: 99%
“…The presence of a clear area surrounding the colony is a signi cant indication of biosurfactant production. Bacteria with positive hemolysis were selected for supplementary tests [13].…”
Section: Hemolytic Activitymentioning
confidence: 99%
“…Saudi Arabia Sabkhas showed that the most commonly isolated bacterial species were Bacillus subtilis and Lactobacillus murinus (Alotaibi et al, 2020). Bacillus spp., on the other hand, were activated at soil polluted with chlorophenol compounds at the industrial zone at Umm-Saied city (Qatar) (Al-Thani et al, 2007;Personal observation). Moreover, most isolates were Gram-positive at rhizosphere soils; few isolates were found Gram-negative, such as the rhizosphere of A. macrostachyum and both rhizosphere and non-rhizosphere of Limonium axillare (Supplementary Figure 3).…”
Section: Bacterial Characterizationmentioning
confidence: 99%
“…However, with the new development of the modern approach, as well as growing awareness among scientists of the role of microorganisms in solving many problems facing mankind, during the last decade, great efforts have been paid to the microbiology of desert soil. Some data (personal observations) indicate that the following bacteria species are present in the raw Qatari soils: ( 1 Other species can also be found, especially when the soil is exposed to various abiotic and biotic factors or treated with organic and inorganic agents from oil and gas activities (such as Bacillus spp., Pseudomonas geniculata and Achromobacter xylosoxidans) (Al-Thani et al, 2007, and some of the above species might be activated and/or thrived under those conditions.…”
Section: Sand Dunesmentioning
confidence: 99%